PORT INVESTMENT AND REGIONAL DEVELOPMENT IN PERU WHAT WOULD BE THE ECONOMIC IMPACT OF THE SAN JUAN DE MARCONA TERMINAL? - CHANG, VICTOR (2024)
THE OBJECTIVE OF THIS DOCUMENT IS TO QUANTIFY THE POTENTIAL IMPACT OF INVESTMENTS IN THE NEW PORT TERMINAL OF SAN JUAN DE MARCONA ON THE ECONOMIC DEVELOPMENT OF THE TERMINAL'S INFLUENCE AREA. TO DETERMINE POTENTIAL EFFECTS, A PANEL DATA APPROACH WAS EMPLOYED USING QUARTERLY INFORMATION FROM 2018 TO 2021, AND THE IMPACT ON PORT TERMINALS WITH SIMILAR CHARACTERISTICS TO THE NEW PORT TERMINAL WAS ASSESSED. THE METHODOLOGY INCLUDED COINTEGRATION ANALYSIS, GRANGER STATISTICAL CAUSALITY, AND ORDINARY LEAST SQUARES ESTIMATIONS OF A POOLED DATASET. RESULTS INDICATE THAT UPON THE COMPLETION OF STAGE 1 OF THE INVESTMENTS, THERE WOULD BE A REAL GDP INCREASE RANGING FROM 10.7% TO 13.2%, AN INCREASE IN LIFE EXPECTANCY AT BIRTH BETWEEN 0.6% AND 1.4%, AN INCREASE IN YEARS OF EDUCATION BETWEEN 10.7% AND 13.2%, AND A 2.6% INCREASE IN EMPLOYMENT. © 2024 BY THE AUTHORS.